Pengembangan Sistem Informasi E-Reporting dalam Pengelolaan Data untuk Budidaya Ikan Berbasis Website di Orion Water - Merli Amelia Anggraeni; Endang Setiawati; Dhany Faizal Racma (Universitas Harapan Bangsa, 2023)
The potential of fish breeding in Indonesia is quite large, supported by Indonesia's diverse natural conditions. This causes water temperatures in the Indonesian region to be relatively stable throughout the year. Fish breeding is one of the activities to maintain, raise, and breed fish and harvest the results in a controlled environment. In conducting fish cultivation there needs to be data processing to monitor in terms of reporting. The owner of Orion Water is one of the people who cultivate fish with an area of 1,000 m2 and more than 20 aquaculture ponds. For now, logging is still using manual or book notes. So that the process of managing large amounts of data that requires time and effort, if the processing of data is not appropriate will result in a recording error that can cause the data to be inaccurate. The difficulties experienced by the owner are also caused by unordinated costs and losses. Therefore, researchers created a web-based E-reporting Information System to facilitate owners in the process of recording data